Changes in macular pigment optical density after full-thickness macular hole closure using inverted flap technique - Michele Rinaldi; Gilda Cennamo; Maria Laura Passaro; Ciro Costagliola (Photodiagnosis and Photodynamic Therapy)
Full-thickness macular hole (FTMH) is a debilitating retinal disorder, particularly in its advanced forms, necessitating surgical intervention for vision restoration. This case report details the successful closure of a large FTMH using the inverted flap technique, highlighting the essential role of multimodal imaging, and particularly macular pigment optical density (MPOD) assessment, in preoperative and postoperative evaluation. A 55-year-old patient presented with severe vision loss in one eye due to a large FTMH. Surgery was performed by an expert vitreoretinal surgeon, resulting in significant postoperative improvements in visual acuity and retinal architecture. Multimodal imaging, including MPOD assessment, played a pivotal role in preoperative evaluation and postoperative monitoring. The notable increase in MPOD following successful surgery suggests its potential role as a valuable adjunctive biomarker associated with a good visual prognosis following this type of macular hole surgical interventions.